(untitled) (Journal of Computational Mathematics, 2004)
A number of new results on sufficient conditions for the solvability and numerical algorithms of the following general algebraic inverse eigenvalue problem are obtained: Given n+1 real n× n matrices A=(a_ij),A_k=(a_ij^(k))(k=1,2,…,n) and n distinct real numbers λ_1,λ_2,…,λ_n, find n real number c_1,c_2,…,c_n such that the matrix A(c)=A+_k=1^nc_k A_k has eigenvalues λ_1,λ_2,…,λ_n.